5x^3y*(-3y)^2+(-6xy)^2*(-xy)+xy^3*(-4x^2)
1个回答
原式=45x^3y^3-36x^3y^3-4x^3y^3=5x^3y^3
很高兴为您解答,【学习宝典】团队为您答题.
请点击下面的【选为满意回答】按钮,
相关问题
计算5x^3y*(-3y)^2+(-6xy)^2*(-xy)-xy^3(-4x)^2
x^3y(-4y)^2+(-7xy)^2*(-xy)-5xy^3*(-3x)^2
3x^y(-4xy^)+5xy*(-6xy)^,其中x=2 y=-1/2
3x^2 y+{xy-[3x^2 y-(4xy^2 +1/2xy)]-(4x^2 y+3/2xy)}
(3xy-9x2-2y2-6xy)-(6x2+2xy-3xy-y)
5x²y-[2²y-(3xy-xy²)-3x²]-2xy²-y
已知:x+y=3,xy=-2,求:1.(3x-4y+2xy)-(2x-5y+5xy)的值;2.(3x-5y+4xy)-(
2x^2-3xy+6y^2-x^2+4xy-5y^2
xy^2=-6,求-xy(X^2Y^5-XY^3-Y)
(3x-4xy-6y)-2(x-4xy+2y)